Structural, Electronic, Vibrational, and Topological Analysis of Single-Walled Zinc Oxide Nanotubes - Marana, Naiara L. [UNESP]; Casassa, Silvia; Longo, Elson [UNESP]; Sambrano, Julio R. [UNESP] (American Chemical Society (ACS), 2016)
Single-walled armchair and zigzag ZnO nanotubes (SWZnONTs) have been studied via periodic computational simulations based on density functional theory with the B3LYP, HSE06, PBE0, and PWGGA functional and all-electron basis set. The influence of the diameter of the nanotubes was carried out with respect to the bond length (Zn-O), bond angles (Zn-O-Zn), energy strain, band gap, density of states (DOS), band structures, vibrational analysis, and topological analysis of the electron density according to the quantum theory of atoms in molecules applied to the solid state. Its nanotubes properties were compared with the ZnO bulk and (0001) monolayer surface. The topological analysis, infrared and Raman spectra, and its vibrational modes at increasing diameter are reported for the first time. Owing to these analysis, both chiralities with large diameter can be used interchangeably in semiconductor applications. These theoretical models can be extended to study further issues, such as the effects caused by the addition of dopant and the interaction of molecules inside and/or outside of the nanotube. (Figure Presented).